LONG-TERM TENDENCIES OF AGRICULTURAL PRODUCTION IN SERBIA: STAGNATION AND FALL - Milanović, Milan R.; Đorovićepoljoprivrede@gmail.com, Milutin; Stevanović, Simo (Economics of Agriculture, 2011)
The trends of the production of agricultural products in Serbia in the past two decades have demonstrated stagnation and fall as well as huge instability of its scope and structure. Having in view the general circumstances in which these trends are taking place, the same can be referred to as a transitional distortion of agriculture and the agrarian market. The dynamics of overall agriculture account for an exceptional cyclic instability, with signifcant differences, not only in the intensity but in the direction of fluctuations, between plant (minus 30/plus 50) and cattle production (the range plus/ minus 10 index points). Apart from the analysis of the production trends, this paper is aimed at establishing different impacts of natural and anthropogenic factors (which means observations in the long run) on basic trends, sectorial features, the scope, structure and reached level of overall agricultural production prior to and after the so-called transition as well, all this activity being based on available statistical and other sources.